Dutch Ships in Tropical Waters The Development of the Dutch East India Company (VOC) Shipping Network in Asia 1595-1660 - Parthesius, Robert (Amsterdamse Gouden Eeuw Reeks, 2010)
The end of the 16th century saw Dutch expansion in Asia, as The Dutch East India Company (the VOC) was fast becoming an Asian power, both political and economic. By 1669, the VOC was the richest private company the world had ever seen. This landmark study looks at perhaps the most important tool in the Company' trading - its ships. In order to reconstruct the complete shipping activities of the VOC, the author created a unique database of the ships' movements, including frigates and other, hitherto ingored, smaller vessels. Parthesius's research into the routes and the types of ships in the service of the VOC proves that it was precisely the wide range of types and sizes of vessels that gave the Company the ability to sail - and continue its profitable trade - the year round. Furthermore, it appears that the VOC commanded at least twice the number of ships than earlier historians have ascertained. Combining the best of maritime and social history, this book will change our understanding of the commercial dynamics of the most successful economic organization of the period.